Observing volcanoes with drones: studies of volcanic plume chemistry with ultralight sensor systems - Karbach, Niklas; Bobrowski, Nicole; Hoffmann, Thorsten (Scientific reports, 2022)
The study of the chemical composition of volcanic emissions is an important method for obtaining information about volcanic systems and providing indirect and unique insights into magmatic processes. However, there is a non-negligible risk associated with sampling directly at volcanic craters or maintaining geochemical monitoring stations at such locations. Spectroscopic remote sensing methods, in turn, can measure only a few species. Here, drones offer the opportunity to bring measurement systems to the scene. Standard parameters that are commonly measured are SO2 and CO2 concentrations, as well as a number of meteorological parameters. The in-flight transmission of data by radio telemetry plays an important role, since visual localization of the volcanic plume from a distance of several kilometers is practically impossible. Until now, larger and quite cost-intensive drones have been used for this purpose, which must first be transported to the site of operation at great expense. Here, we present the development and successful deployment of a very small drone system (empty weight < 0.9 kg) for chemical characterization of volcanic plumes that can be easily transported on foot to difficult-to-access terrain and, moreover, requires only minimal flight and administrative preparations for operation as an aerial observation platform.
Gesehen am 16.01.2023